Dependence of elastic and optical properties on surface terminated groups in two-dimensional MXene monolayers: a first-principles study. Issue 42 (12th April 2016) - Bai, Yuelei; Zhou, Kun; Srikanth, Narasimalu; Pang, John H. L.; He, Xiaodong; Wang, Rongguo
Abstract : The low adsorption and reflectivity from infrared to ultraviolet rays account for the high transmittance of Ti3 C2 T2 that has been experimentally observed, and it is predicted that Ti2 CT2 will have higher optical transmittance in this range. Abstract : Density functional theory is used to investigate the elastic and optical properties as well as the crystal and electronic structures of two-dimensional Ti2 CT2 and Ti3 C2 T2 (T = F, O, and OH) MXene monolayers. It is found that the elastic stiffness, optical response, crystal structure and the electronic structure show strong dependence on the surface terminated groups often formed with MXene during the etching process. The elastic stiffness maintains only with the surface termination of O atoms, but a large degradation is present in the surface terminations of F and OH atoms. The low adsorption and reflectivity in the range from infrared to ultraviolet rays account for the high transmittance of Ti3 C2 T2 that has been experimentally observed, and it is predicted that Ti2 CT2 will have higher optical transmittance in this range. The calculations also demonstrate the presence of the optical bandgap in Ti2 CO2, which renders its potential applications in optical and electronic devices.